1998
DOI: 10.1002/j.1556-6676.1998.tb02390.x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Client and Counselor Variables That Influence Likelihood of Counselor Self‐Disclosure

Abstract: Selected client and counselor variables affecting reported likelihood of self‐disclosure by 120 experienced clinicians in relation to four scenarios were examined. Variables included client age and diagnosis and counselor gender, experience, and exposure to disclosing counselors in their own experience of counseling. Disclosure likelihood was greatest for high ego‐strength diagnoses and for respondents who reported positive disclosures from counselors in their own counseling experiences. Reasons for and agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 12 publications
(45 reference statements)
2
37
0
1
Order By: Relevance
“…These reasons correspond with the overall literature on therapist self-disclosure and reported reasons for not disclosing. For example, Simone et al (1998) found that counselors chose to not self-disclose primarily due to boundary issues among other reasons. Boundary issues seemed especially salient for female recovering counselors in this study due to experiences of inappropriate treatment by male clients who learned of their recovery status.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…These reasons correspond with the overall literature on therapist self-disclosure and reported reasons for not disclosing. For example, Simone et al (1998) found that counselors chose to not self-disclose primarily due to boundary issues among other reasons. Boundary issues seemed especially salient for female recovering counselors in this study due to experiences of inappropriate treatment by male clients who learned of their recovery status.…”
Section: Discussionmentioning
confidence: 97%
“…Lastly, in both studies there seems to be a degree of skepticism associated with self-disclosure in that it may at times be overused or used for the wrong reasons, perhaps a mistake made more often by those new in recovery and new in the substance abuse field. As noted above, these reasons are also addressed in the general self-disclosure literature, mostly framed as concerns associated with boundary issues (Simone et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In an experimental study, Barrett and Berman (2001) found that more experienced psychotherapists increased selfdisclosing more than did inexperienced when advised to do so. On the other hand, Simone, McCarthy, and Skay (1998) found no differences due to age or experience when psychotherapists were asked to report whether they would use self-disclosure in four given situations. Skovholt and Rönnestad (1992) have presented a model of psychotherapists' development that basically implies that more experienced psychotherapists usually feel freer to use their own ideas instead of manual-based instructions and that they tend to feel free to disclose their own experiences to a higher degree than younger psychotherapists.…”
Section: Frequencymentioning
confidence: 98%